PENGARUH CAPITAL INTENSITY, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Empiris pada Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2023) - Musyafiq, Nazrul; Mansur, Fitrini; Safelia, Nela (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to determine the Effect of Capital Intensity, Sales Growth and Firm Size on Tax avoidance . The independent variables used in this study are Capital Intensity, Sales Growth and Firm Size. While the dependent variable in the study is Tax avoidance . This type of research is quantitative research. The population in the study were Properti and Real Estate companies listed on the Indonesia Stock Exchange for the period 2022-2023. The sample in this study was taken using the purposive sampling method with a sample size of 33 companies. The data analysis used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange. The analysis technique used is data regression using the help of E-Views 12 software. The results of this study indicate that Capital Intensity has no effect on Tax avoidance . While Sales Growth and Firm Size have a negative effect on Tax avoidance.